Internal documents of corporations as a source of the legal regulation of internal corporate relations in Russia and Azerbaijan - V Y Ifraimov (RUDN Journal of Law, 2013)
Relationships developed in the different corporations, to a greater extent governed by its internal documents. Internal documents of corporations shall be based on the law and other legal acts are adopted by the corporation and shall apply to all subjects of internal corporate relations. In this article, the author conducts a comparative legal study of the provisions of internal corporate documents in Russia and Azerbaijan.